PERUBAHAN EKSPRESI KONSEP NATAH DALAM TATA RUANG DI BALI - Made Putra, I Gusti (Jurnal Natah; Vol. 1, No. 2 Juni 2003, 2012)
Natah is a common term to express a main space at the center of a built environment such as a house, a village, and a town. This article is based on the observation of about 30 houses, 25 villages, and 23 civic centres of both from traditional type and modern type. Natah in a house is formed by the setting of building masses surround it, natah in a village is formed by dwelling and public facilities, and natah in a town is formed by a civic centre and a number of urban facilities. Natah has three main functions: social, ritual, and environmental. The meaning of a natah is as a media allowing the encounter of the sky (male character-purusa) and the earth (female character – pradana) and acting as the center of both building masses orientation and human circulation orientation. According to the development of the community, changes are also occur on the form, function, and the meaning of natah.
Keywords: form, function and meaning.